(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The interannual ocean-atmosphere anomaly of the El Nino Southern Oscillation (ENSO) and Indian Ocean Dipole Mode (IODM) events that prevail in the tropical Indo-Pacific region impacts significantly on regional marine ecosystem, hydrology and climate variabilities. This study aims to investigate spatial pattern and temporal variability of sea surface temperature (SST) and surface chlorophyll-a (Chl-a), related to ENSO and IODM in the region. The monthly data time-series (1980-2017) were obtained from global data center, and were analyzed by applying the empirical orthogonal function (EOF) methods. The results show that the first three eigen values of SST (Chl-a) explained for 81.7% (76%) of total variance. Spatial pattern of SST EOF mode-1 (56%) formed an asimetric dipole-like shape between eastern and western tropical Pacific with a distinct pattern in upwelling region off Peru waters. This pattern may be associated with ’normal’ or La Nina events. Furthermore, El Nino and IODM condition may be depicted from SST mode-2 (19%), in which negative phase contours were predominant over equatorial Pacific and disappearing ’upwelling region’ off Peru waters.